The efficacy and safety of Epimedium in the treatment of primary osteoporosis: a systematic review and meta-analysis - Zhang, Xian-Quan; Hua, Zhen-Hui; Huang, Chu-Jia; Chen, Hai-Yun; Hu, Zong-Ren; Zhang, Mei-Ren; Liu, Jun (Frontiers in Medicine, 2025)
BackgroundPrimary Osteoporosis (POP) is a global public health issue, and traditional medications have long-term safety concerns. Epimedium, a kidney-tonifying traditional Chinese medicine (TCM), has the potential to regulate bone metabolism through multiple targets, but clinical evidence is scattered and inconclusive.ObjectiveThis systematic review and meta-analysis aim to evaluate the efficacy and safety of Epimedium and its active components in treating POP.MethodComputer searches were conducted in multiple domestic and international databases, including PubMed, Embase, Cochrane Library, China National Knowledge Infrastructure (CNKI), and Wanfang Database, to collect randomized controlled trials (RCTs) comparing the use of Epimedium as an adjunct or alternative therapy with traditional drug treatments for POP. Literature was screened according to predefined inclusion and exclusion criteria, quality assessments were performed on eligible articles, relevant data were extracted, and statistical analysis was conducted using RevMan 5.4 software.ResultsA total of 10 RCTs were included, with a final inclusion of 890 cases, 448 in the experimental group and 442 in the control group. Meta-analysis suggests that the overall efficacy rate of the Epimedium group was significantly higher than that of the control group (OR = 3.80; 95% CI: 2.27,6.37; p = 0.0001). Compared with the control group, Epimedium group’s Lumbar vertebra bone mineral density (BMD) (SMD = 1.15; 95% CI: 0.61,1.70; p < 0.0001), Femoral neck BMD (SMD = 1.11; 95% CI: 0.58,1.65; p < 0.0001), Distal radius BMD (SMD = 1.27; 95% CI: 0.57,1.98; p = 0.0004), and Metacarpal BMD (MD = 0.04; 95% CI: 0.04,0.12; p < 0.0001) all showed significant improvement, with a shorter time to relief of lower back pain (MD = -11.38; 95% CI: −12.63, −10.12; p < 0.00001). Serum alkaline phosphatase (ALP) was significantly reduced (MD = -8.78; 95% CI: −12.80, −4.77; <0.0001), while bone-specific alkaline phosphatase (BALP) increased (MD = 6.73; 95% CI: 3.32,10.14; p = 0.0001). Adverse reactions were low, mainly mild gastrointestinal reactions or skin allergies.ConclusionEpimedium can effectively improve bone density and clinical symptoms in patients with POP, with good safety, making it a potential alternative or adjunctive treatment option, but more high-quality studies are needed to verify long-term efficacy.